Prediction of genetic value for sweet cherry fruit maturity among environments using a 6K SNP array. Issue 1 (1st January 2019) - Hardner, Craig M; Hayes, Ben J; Kumar, Satish; Vanderzande, Stijn; Cai, Lichun; Piaskowski, Julia; Quero-Garcia, José; Campoy, José Antonio; Barreneche, Teresa; Giovannini, Daniela; Liverani, Alessandro; Charlot, Gérard; et al.
Abstract: The timing of fruit maturity is an important trait in sweet cherry production and breeding. Phenotypic variation for phenology of fruit maturity in sweet cherry appears to be under strong genetic control, but that control might be complicated by phenotypic instability across environments. Although such genotype-by-environment interaction (G × E) is a common phenomenon in crop plants, knowledge about it is lacking for fruit maturity timing and other sweet cherry traits. In this study, 1673 genome-wide SNP markers were used to estimate genomic relationships among 597 weakly pedigree-connected individuals evaluated over two seasons at three locations in Europe and one location in the USA, thus sampling eight 'environments'. The combined dataset enabled a single meta-analysis to investigate the environmental stability of genomic predictions. Linkage disequilibrium among marker loci declined rapidly with physical distance, and ordination of the relationship matrix suggested no strong structure among germplasm. The most parsimonious G × E model allowed heterogeneous genetic variance and pairwise covariances among environments. Narrow-sense genomic heritability was very high (0.60–0.83), as was accuracy of predicted breeding values (>0.62). Average correlation of additive effects among environments was high (0.96) and breeding values were highly correlated across locations. Results indicated that genomic models can be used in cherry to accurately predict date of fruit maturity for untested individuals in new environments. Limited G × E for this trait indicated that phenotypes of individuals will be stable across similar environments. Equivalent analyses for other sweet cherry traits, for which multiple years of data are commonly available among breeders and cultivar testers, would be informative for predicting performance of elite selections and cultivars in new environments. Genetics: Sweet news for cherry breeders Or Genetics: Cherry-ripening is predictable in new environments: The fruiting season of a cherry is short and sweet, but at least it's relatively consistent across different environments, a new genetic analysis suggests. The development of additional early- and late-maturing sweet cherry cultivars is a major objective for cherry-breeders, but the influence of the environment on the timing of fruit maturity—which could reduce the accuracy of selective breeding efforts - was unclear. So, Craig Hardner at the University of Queensland in St Lucia and colleagues used DNA markers to  model relationships among individuals and examined the dates at which their fruit ripened at four different locations in Europe and the USA across two seasons. The timing of fruit maturity was relatively stable between related individuals across similar environments, suggesting that new cherry cultivars could be developed without having to test them at multiple sites.